Quantitative analysis of fine needle aspiration biopsy samples - Rajer, Mirjana (Radiology and oncology (Ljubljana), 2005)
The fine needle aspiration biopsy (FNAB) is one of the methods used in tumour evaluation. Since a certain number of tumour cells are needed for a complete diagnostic algorithem, we wanted to test how many cells remain in the needle and syringe after routine stains have been made and which factors influence this number. The remaining cells are used in ancillary diagnostic procedures. Material and methods. One hundred fifty two FNAB samples of tumours of the breast, thyroid and lymph nodes were included in our study. We counted the cells which were left in the needle and the syringe after the standard smears had been made. Buerker-Tuerks chamber was used for this purpose. Results. The number of cells depended on the organ from which the cells had been aspirated,on the type of tumour and, in the case of breast cancer, also on thelevel of experience of the FNAB performer. The percentage of samples with too few cells for all modern diagnostic methods (<5x105) is lowest in FNAB of lymph nodes (4.9%), followed by breast (16.7%) and thyroid (18%). Conclusions.We concluded that FNAB in the majority of cases grants a sufficient number of cells for the standard microscopic evaluation and also ancillary diagnostic procedures.
Keywords: aspiracijska biopsija; diagnostika; novotvorbe; rak (medicina); tumor